Effect of Ball Milling under Various Conditions on Several Physicochemical Properties of Rock Phosphate Fertilizer - JOKO PRIYONO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
A laboratory study was conducted to identify the effects of milling under various conditions, including use of water and potassium as milling lubricants, on several physicochemical properties of rock phosphate fertilizer. The identified properties were the XRD patterns, particle size distribution, surface area, and NaHCO3-extractable P of the fertilizer. Milling for 2 hourssignificantly reduced particle size, promoted amorphization,increased surface area and amount of extractable P in 1N NaHCO3 of rock phosphate fertilizer, with those effects for dry milling were much greater than for wet milling. Wet milling and use of additives (KCl and K-feldspar) minimized the occurrence of agglomeration during milling process. Although further tests in soil-plant system are required, dry milling may be recommended as a simple method for manufacturing an agronomically effective P + K fertilizer.